3 Investigating the utility of subcutaneous implantable cardioverter-defibrillators in the adult congenital heart disease population. (2nd February 2018) - Garside, H; Bono, J de; Hudsmith, L; Leyva-Leon, F
Abstract : Purpose: The subcutaneous implantable cardiac defibrillator ICD (S-ICD) has been developed to reduce the risk of lead complications in patients requiring prophylactic ICDs. It has also been recommended for patients with adult congenital heart disease (ACHD) who are at risk of sudden cardiac death (SCD) and often have complex cardiac anatomy, preventing the implantation of a transvenous system. It is unclear how many patients with ACHD may be suitable for a S-ICD. Methods: The S-ICD screening protocol was carried out in three ACHD populations; Tetralogy of Fallot (TOF), complete transposition of the great arteries (d-TGA) and Fontan. S-ICD eligibility and potential predictors of ineligibility were investigated. Results: 102 patients were recruited to this study, with 14 repeating the protocol post-exercise. Mean age was 27 (±15 years) and 53% male. 25 participants failed to meet the S-ICD screening criteria and were deemed ineligible, (23.5%), significantly greater than the proportion of ineligible patients in the general ICD population (p≤0.01). Exercise was not shown to have a significant impact on eligibility. A broad QRS duration, small R:TMAX and a large RVEDV were associated with ineligibility. Conclusion: This data suggests that a significant proportion of ACHD patients would not be candidates for the S-ICD, due to the risk of inappropriate sensing. This emphasises an importance of alternative treatment options for this population at a high risk of SCD. Substantial development of the current S-ICD sensing algorithm would be required to increase eligibility.